Pengaruh Pelatihan Terhadap Kinerja Yang Dimediasi Motivasi Pada Perawat Di Rumah Sakit Kabupaten Bekasi - Nugraha, Kiky Aristiana; Budiyanto, Eri; Setyaningrum, Retno Purwani (Peneliti.net, 2025)
This study aims to analyze the effect of training on nurse performance in hospitals, with motivation as a mediator variable. The research was conducted at Bekasi Regency Hospital by involving nurses as the object of research and a total sample of 96 respondents. The method used was quantitative with a case study design, where data were collected through questionnaires measured on a Likert scale and analyzed using SmartPLS 3.0 tools. The results showed that training has a positive effect on nurse performance, training has a positive effect on motivation, motivation has a positive effect on nurse performance and work motivation acts as a significant mediator for the effect of training on nurse motivation.